The importance of body image disturbances for the outcome of outpatient psychotherapy in patients with anorexia nervosa: results of the ANTOP-study - Junne, Florian; Wild, Beate; Herzog, Wolfgang (European eating disorders review, 2019)
This study investigates the role of body image self-appraisal in predicting the outcomes of outpatient psychotherapy in patients with anorexia nervosa (AN). Multiple linear regression analyses and a path-analysis model were applied to test the study hypotheses that body image at baseline predicts treatment outcomes of outpatient psychotherapy in patients with AN at follow-up measurement. The analyses were conducted as secondary analyses in a subgroup (n = 148) of the anorexia nervosa treatment of outpatient-cohort (ANTOP-study) (N = 242) of patients with AN. The results show that Negative Evaluation of the Body at baseline predicts perceived stress during psychotherapy, which in turn predicts depressive symptoms at the end of therapy which in turn predicts the outcomes body mass index and EDI-2 sum score at 12 months follow-up. The results underline the importance of body image disturbance in the course of AN and call for body image as a central target of psychotherapeutic interventions in patients with AN.
First published: 16 July 2018
Gesehen am 24.07.2019